2021
DOI: 10.1177/08982643211055032
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Personality Measures and Perceived Mental Fatigability

Abstract: Objective Examine the association between personality measures and perceived mental fatigability. Methods We performed a cross-sectional analysis in N=1670 men, age 84.3±4.1 years. Multivariable linear regression models were used to examine the covariate adjusted association between personality measures (conscientiousness, optimism, goal reengagement, and goal disengagement) and perceived mental fatigability (measured with the validated 10-item Pittsburgh Fatigability Scale, PFS). Results One standard deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…An intervention study showed that for people with a high level of conscientiousness, their step count was positively predicted from a pre-test, while under monitoring during the intervention, people with a high level of neuroticism showed a significant increase in their daily step counts as well [ 30 ]. Meanwhile, people with a sense of openness tended to be slightly more active, but there were no significant differences in the level of leisure-based physical activity among people with agreeableness [ 31 , 33 , 34 ]. In addition to people with high neuroticism, people with other types of personality traits were associated with a high level of engagement in leisure activities, including social and physical activities, which indicates successful active aging [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An intervention study showed that for people with a high level of conscientiousness, their step count was positively predicted from a pre-test, while under monitoring during the intervention, people with a high level of neuroticism showed a significant increase in their daily step counts as well [ 30 ]. Meanwhile, people with a sense of openness tended to be slightly more active, but there were no significant differences in the level of leisure-based physical activity among people with agreeableness [ 31 , 33 , 34 ]. In addition to people with high neuroticism, people with other types of personality traits were associated with a high level of engagement in leisure activities, including social and physical activities, which indicates successful active aging [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Briki and Dagot [ 25 ] demonstrated that dispositional self-control and perceived goal progress were negatively associated with neurotic self-attentiveness, thus negatively predicting subjective well-being. Furthermore, people with lower levels of conscientiousness and optimism are associated with low goal re-engagement, higher mental fatigability, and poorer physical and cognitive health maintenance [ 33 ]. Meanwhile, optimism and conscientiousness are positively associated with goal achievement, adjustments, and re-engagement and thus are related to older adults’ participating in physical activity and having a healthy quality of life [ 30 ].…”
Section: Resultsmentioning
confidence: 99%